STRUCTURED PHYSICAL CULTURE AS A PSYCHOPHYSIOLOGICAL STRATEGY FOR REDUCING DIGITAL FATIGUE AMONG UNIVERSITY STUDENTS (American Journal of Interdisciplinary Research and Development, 2026)
In the digital transformation of higher education, students spend an increasing part of their academic and personal life in front of screens, which changes not only the method of learning but also the structure of movement, rest, communication and self-regulation. The article examines structured physical culture as a psychophysiological and pedagogical strategy for reducing digital fatigue among university students. Digital fatigue is interpreted as a complex condition that includes visual strain, sedentary overload, attention fragmentation, emotional tension, sleep instability, reduced motivation and weakening of bodily self-awareness. The purpose of the study is to justify a model in which physical culture functions not merely as a discipline for developing motor skills, but as a health-preserving educational mechanism that compensates for sedentary screen-based learning and supports mental well-being. The research is based on theoretical analysis, comparative synthesis of scientific sources, interpretation of international physical activity recommendations and pedagogical modeling. The proposed model includes four components: motor activation, psychophysiological recovery, digital-hygienic education and reflective self-monitoring. The article argues that moderate aerobic exercises, posture correction, mobility tasks, breathing regulation, group movement and short active breaks can reduce the consequences of digital overload by restoring circulation, improving muscle tone, stabilizing emotional state and strengthening self-control. It is concluded that physical culture in the digital era should be integrated into university strategies of student well-being, because the culture of movement is becoming a necessary condition for sustainable learning, mental resilience and responsible digital behavior.